Stab Wound Extension for the Eviscerated Small Bowel with Severe Ischemic Changes - Chan Kyu Lee; Chan Yong Park; Kwang Hee Yeo; Ho Hyun Kim (Journal of Acute Care Surgery, 2018)
An abdominal stab wound with evisceration is an indication of an emergency laparotomy. We encountered a case of a very severe ischemic change in the eviscerated small bowel as a result of stabbing. The patient was considered to have a high possibility of progressing to strangulation of the small bowel. Therefore, a stab wound extension was performed as a decompression in the emergency department before definite surgery in the operating room. Most of the small bowel could be saved except for the segment with the damage caused by the stab injury. The patient was discharged without complications.